In vitro toxicity assessment of paints with antimicrobial properties - a comparative study - Machado-Querido, M. (2022)
Abstract publicado em: Toxicol Lett. 2021 Sep;350(Suppl):S212. https://doi.org/10.1016/S0378-4274(21)00229-0